2014
DOI: 10.1371/journal.pone.0114709
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neutralizing Antibody Responses Elicited from Highly Diverse Polyvalent Heterotrimeric HIV-1 gp140 Cocktail Immunogens versus a Monovalent Counterpart in Rhesus Macaques

Abstract: Eliciting neutralizing antibodies capable of inactivating a broad spectrum of HIV-1 strains is a major goal of HIV-1 vaccine design. The challenge is that envelopes (Envs) of circulating viruses are almost certainly different from any Env used in a vaccine. A novel immunogen composed of a highly diverse set of gp140 Envs including subtypes A, B, C, D and F was developed to stimulate a more cross-neutralizing antibody response. Env heterotrimers composed of up to 54 different gp140s were produced with the aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…We have previously demonstrated that Carbopol elicits strong Th1-type T and B-cell responses in mice, mediating protection from otherwise lethal influenza infection, and anti-tumor responses [22] . We observed that Carbopol did not have obvious toxicity in mice [22] or non-human primates [23] , and propose that this type of polymer might have utility as a human vaccine adjuvant.…”
Section: Introductionmentioning
confidence: 73%
“…We have previously demonstrated that Carbopol elicits strong Th1-type T and B-cell responses in mice, mediating protection from otherwise lethal influenza infection, and anti-tumor responses [22] . We observed that Carbopol did not have obvious toxicity in mice [22] or non-human primates [23] , and propose that this type of polymer might have utility as a human vaccine adjuvant.…”
Section: Introductionmentioning
confidence: 73%
“…Despite many attempts (12)(13)(14)(78)(79)(80), generation of bNAb against tier 2 HIV-1 primary isolates by vaccination remains an unmet goal. Several recent studies have succeeded in demonstrating vaccine-induced NAb against autologous tier 2 virus or a panel of mutated tier 2 isolates with increased CD4 or V3 epitope exposure (12)(13)(14)21).…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies b12 ( 28 ), NIH45-46 ( 29 ), VRC01, VRC03 ( 30 ), 412D ( 31 ), A32 ( 32 ), C11 ( 33 ), CH01 ( 34 ), PGT145 ( 29 ), 2G12 ( 35 ), PGT121 ( 29 ), PGT128 ( 29 ), PGT135 ( 29 ), 14E, 19b, 39F ( 36 ), 35O22 ( 37 ), 3BC176, 3BC315 ( 38 ), PGT151 ( 39 ), CAP256-VRC26.08 ( 40 ), PDGM1400 ( 41 ), and 7B2 ( 42 ) were expressed in freestyle 293F cells under serum-free conditions and purified by protein A chromatography as previously described ( 43 ). Soluble CD4 (sCD4) ( 44 ), CD4-IgG2 ( 45 ), 15e, F105, 17b ( 46 ), PG16 ( 47 ), and b6 ( 28 ) were from the IAVI Neutralizing Antibody Consortium.…”
Section: Methodsmentioning
confidence: 99%